Bioactivity Examination of Uncaria gambir (W.Hunter) Roxb on In Vitro Human Sperm Motility - Silvani Permatasari; Nida Halisa; Agnes Frethernety (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2023)
Globally, 48 million couples experience infertility, where male infertility factors contribute to 50% of cases. Spermatozoa motility is a crucial parameter in assessing male fertility. Antioxidants act as the body's defence against excessive ROS and can be used as a treatment for male infertility. One of the local plants in Central Kalimantan that is potentially rich in antioxidants is Bajakah Kalalawit (Uncaria gambir (W.Hunter) Roxb. However, there is limited research on the bioactivity of Bajakah Kalalawit on spermatozoa in vitro. This study aims to determine the effect of ethanol extract of Uncaria gambir (W. Hunter) Roxb on spermatozoa motility in vitro. Bajakah Kalalawit stems were extracted using a 3x24-hour maceration technique with 96% ethanol. After obtaining the concentrated extract, the secondary metabolite compound content was analyzed through a phytochemical screening. The sample used was in vitro human spermatozoa that were washed and added to Bigger Whitten Whittingham medium, then incubated at 37°C for 1 hour with a 96% ethanol extract of Bajakah Kalalawit at doses of 50ng/ml, 100ng/ml, 500ng/ml, and 1000ng/ml, as well as a control group (Bigger, Whitten & Whittingham medium only). The results showed that the compounds contained in the ethanol extract of Uncaria gambir (W.Hunter) Roxb were terpenoids, flavonoids, phenolics, steroids, saponins, alkaloids, and tannins. Spermatozoa motility significantly increased in the treatment groups starting from doses of 50ng/ml, 100ng/ml, 500ng/ml, and 1000ng/ml compared to the control group. Ethanol extract of Uncaria gambir (W.Hunter) Roxb could increase spermatozoa motility in vitro and succeeded in improving reproductive technology.